The Effect of Language on Eye-Witness Testimony - Tan, Diana (Journal of Malaysian and Comparative Law, 2019)
An awareness of the significant role language plays in the legal process is not a recent development. This issue, particularly in relation to courtroom testimony, has been of concern to many since the early 1900s. This paper reports on some of the empirical research that seem to suggest strongly that "eye-witness testimony is extremely vulnerable to linguistic engineering".